Digital Learning 5.0: Leveraging Adaptive, Immersive, and Inclusive Technologies to Overcome Educational Inequity - Duwi Purnama Sidik; Fitri Irawijayanti; Abdullah Baihaqi (JINEA: Journal of Innovation in Education and Learning, 2025)
Digital Learning 5.0, emphasizing adaptability, immersion, and inclusivity, offers a promising approach to reducing educational inequities. This study aims to examine how these technologies are conceptualized and implemented to enhance equitable learning opportunities. A qualitative case study was conducted through an integrative literature review, analyzing peer-reviewed articles, conference proceedings, and authoritative reports from major databases. Data were synthesized to identify key strategies, frameworks, and outcomes of Digital Learning 5.0 across diverse educational contexts. Findings reveal that combining adaptive learning platforms with immersive and inclusive features creates an engaging, personalized, and accessible learning ecosystem. This approach improves learner motivation, knowledge retention, academic performance, and equitable access for students, including those with disabilities and from underrepresented backgrounds. The study underscores the importance of strategic investment, professional development, and inclusive design in education, providing practical and policy implications for implementing Digital Learning 5.0 to achieve high-quality and equitable learning outcomes.